Design of A QoS-Aware Service Composition and Management System in Peer-to-Peer Network Aided by DEVS - Hengheng Xie; Boukerche, A.; Ming Zhang; Zeigler, B.P. (2008 12th IEEE/ACM International Symposium on Distributed Simulation and Real-Time Applications, 2008)
QoS-aware service management and composition has become an interesting research topic with the rapid development of service oriented architecture (SOA). Differently with Web-services based systems, the emergence of peer-to-peer (P2P) based distributed network technology brings more challenge to the QoS-aware service management and composition. In this paper, we propose our design of a QoS-aware hierarchical service composition and management system in a context of JXTA-enabled P2P network. We conducted a comparison experiment of our design with commonly used flat-based service composition and management, and found that our design outperforms the flat-based one in terms of a higher success rate for satisfying the user's QoS requirement. Furthermore, we used a RT-DEVS model based formal approach to validate our design, and believe that it can be a promising technology in aiding the design of an efficient QoS-aware service composition and management system.